PEMANFAATAN LUMPUR SIDOARJO SEBAGAI BAHAN MENTAH GLASIR STONEWARE - Supriyadi, Supriyadi; Cingah, Made; Suardana, Putu (BULETIN FISIKA, 2012)
Have been made 3 (three) glaze formula with Sidoarjo mud, Pecatu lime and Lodoyo felspar as the component. The glazes are compatible applied to stoneware bodies because the mature temperature is so similar with the sintering temperature of stoneware bodies.These glazes have started to mature after fired at 1240 o C and not yet destroyed at 1280 o C. The glazes are melting enough, theirs color are yellow, greenish and yellow with red spot with smooth surface. The first glaze (coded by LS - 1) which made by mixture 40 % (w) Sidoarjo mud, 15 % (w) Pecatu lime and 45 % (w) Lodoyo feldspar give yellow slight gloss glaze. The second glaze (coded by LS – 2) which have formula 40 % (w) Sidoarjo mud, 25 % (w) Pecatu lime and 35 % (w) Lodoyo feldspar is greenish semi gloss glaze. The last one (coded by LS – 3) which made by mixture of 50 % (w) Sidoarjo mud, 20 % (w) Pecatu lime and 30 % (w) Lodoyo feldspar give dop glaze with unique texture.